HUBUNGAN ANTARA JENIS, PORSI DAN FREKUENSI MAKAN DENGAN GEJALA GERD PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA TAHUN 2020 - Tri Handayani Setyaningrum, (2020)
Gastroesophageal reflux disease ( GERD ) is a pathological condition caused by reflux of stomach contents into esophagus. The onset of GERD symptoms can be caused due to consuming foods that irritate the stomach, excessive meal portions and irregularity of eating frequency. This study aims to determine the relationship between type, portions and frequency of meals with GERD symptoms among students of the Faculty of Medicine Pembangunan Nasional Jakarta University. This is an analytic observational research with cross sectional design. Ninety three students were taken as samples using stratified random sampling. The research instrument used a questionnaire to assess the type of food, meal portion and frequency, while GERDQ used to assess GERD symptoms. Data were analyzed using the Chi-squared test and Logistic Regression test. The results of the analysis of bivariate with Chi-square test found that there is a significant relationship between the type of meal (p = 0.022) and the portion of meal (p = 0.040) with the GERD symptoms. Type of food is the most influencing factor (OR: 3.977) on the GERD symptoms. The more often someone consumes foods that are irritating, the higher the risk of experiencing GERD symptoms .